RCC Dam Design Concept Of The Sungai Kinta Dam (SKD) Perak - Abang Abdullah, Dayang Norehan (Universiti Sains Malaysia, 2006)
This case study is based on Sungai Kinta Dam and situated in Kinta, Perak. This dam was designed using the Roller-Compacted Concrete (RCC) method. This case study is focused on Roller-Compacted Concrete design concept of Sungai Kinta Dam (SKD). The study was done to evaluate the advantages of using Roller Compacted Concrete with respect to the cost, the time of construction, the materials and the selected location. The risk of Sungai Kinta Dam project to environmental impact was also done. The literature review and questionnaire were used to get data for Sungai Kinta Dam project. The analysis shows that the SKD give advantages due to cost effectiveness, short in time of construction, quality in materials, suitable to the location, economic and low impact to environment. But the major threat to Sungai Kinta Dam is soil erosion.